IPO market cycles and expansion curse: Evidence from Chinese IPO market. (28th October 2016) - Jin, Yonghong; Guo, Jianbang; Zhou, Xiaozhou; Li, Sai-Ping
ABSTRACT: There are two theories on the relationship between primary and secondary markets for securities. The first states that the expansion of IPO financing leads to a decline in stock prices, i.e. an expansion curse effect. The other states that the stock index cycle leads to a corresponding periodic change in the amount of IPO financing, i.e. the IPO market cycle theory. This paper studies the relationship between the security issuing market and the trading market in China. On the aspect of the impact of the primary market on the secondary market, an expansion curse exists in bear markets but is not significant in bull markets. On the aspect of the impact of the secondary market on the primary market, such impact exists in bull markets but is not significant in bear markets. The results provide an explanation for phenomena such as 'short bull markets and long bear markets', and excessive price fluctuations in Chinese security markets.